Assessing Organizational Learning Capacity among Clinical Laboratories of General Teaching Hospitals Affiliated to Tehran University of Medical Sciences - Hossien Dargahi; Alia Akbar Razghandi; Zeynab , Rajab Nezhad (Tehran University of Medical Sciences, 2016)
Background: Concerning to the importance of team learning and process change, the clinical laboratories employees should be familiar with organizational learning. This study aimed at assessing and determining organizational learning capability among clinical laboratories employees of Tehran University of Medical Sciences hospitals. Materials and Methods: This study was a descriptive-analytical and cross-sectional one which conducted among 85 employees of clinical laboratories using Cochran formula at five general teaching hospitals of Tehran University of Medical Sciences. The research instrument was Gomez et al. questionnaire consisted of four dimensions such management commitment, systematic approach, open climate and knowledge transfer in 17 questions. Five point Likert scale was used to rank questions. SPSS software 19 version was utilized to data analysis using t- test, Pearson Correlation Coefficient and Welch method. Results: The average score of organizational learning among employees of studied clinical laboratories was 3.11 which showed relative desirable situation. Also, management commitment as an element of organizational learning had significant difference among the clinical laboratories (p=0.002). There was a significant relationship between employees education level with knowledge transfer and integration capability (p=0.04). Conclusion: The process of organizational learning capability of the studied clinical laboratories was not desirable. Therefore, in order to complete establishment of organizational learning in clinical laboratories, should pay attention to some elements such establishment of patient safety system, initiation of error registration system and encouraging employees to report the errors